Moderation in Fatwas and Ijtihad: An Analysis of Fatwas Issued by the MKI Malaysia Concerning the Covid-19 Pandemic - Abdul Manan Ismail; Ahmad Syukran Baharuddin (AHKAM : Jurnal Ilmu Syariah, 2022)
Certain muftis reject the moderation method when giving fatwas. They are more prone to extremism or dereliction approaches. This rejection occurs due to various causes and, if left unaddressed, will have a detrimental impact on the fatwa institutions, muftis, and mustaftis. This research discussed the notion of moderation in Islam and how it is applied in the realm of a fatwa. Given that Malaysia is currently dealing with the COVID-19 pandemic and that the MKI (Majlis Kebangsaan Bagi Hal Ehwal Ugama Islam) has issued several fatwas on it, this research will look into the fatwas and the features of moderation inherent within it. Using Bowen's document analysis methodology, this study was performed qualitatively by gathering pertinent data from primary and secondary documents. The retrieved data from both documents were analyzed using content analysis methodology to get valuable information and rearrange it to produce meaning that could be understood and digested. The findings demonstrate that moderation is a symbol of Islam and that one of Islam's virtues is to conduct religious affairs and issue rulings with moderation. In fatwas, the notion of moderation centers on facilitating Muslims' religious experiences. In the context of the MKI fatwas, this study discovered that five fatwas were issued on Islamic affairs during the COVID-19 pandemic. According to the findings of this study, each fatwa has its features of moderation.   AbstrakBeberapa mufti tertentu menolak menerapkan moderasi saat memberikan fatwa. Mereka lebih rentan terhadap pendekatan ekstremisme atau kelalaian. Penolakan ini terjadi karena berbagai sebab. Hal itu jika dibiarkan akan berdampak merugikan bagi lembaga fatwa, mufti, dan para mustafti. Untuk itu, penelitian ini dilakukan dengan tujuan untuk membahas pengertian moderasi dalam Islam dan bagaimana penerapannya dalam konteks fatwa. Mengingat bahwa Malaysia saat ini sedang berurusan dengan pandemi COVID-19 dan bahwa MKI (Majlis Kebangsaan Bagi Hal Ehwal Ugama Islam Malaysia) telah mengeluarkan beberapa fatwa yang berkaitan hal tersebut. Penelitian ini akan melihat fatwa-fatwa tersebut dan bentuk moderasi yang melekat di dalamnya. Untuk menjelaskan rumusan masalah dan tujuannya, penelitian ini menggunakan pendekatan kualitatif dengan mengumpulkan data terkait dari dokumen primer dan sekunder menggunakan metodologi analisis dokumen Bowen. Data yang diperoleh dari kedua jenis dokumen tersebut dianalisis menggunakan metodologi analisis isi untuk mendapatkan informasi yang berharga dan disusun kembali untuk menghasilkan makna yang dapat dipahami dan dicerna. Temuan menunjukkan bahwa moderasi adalah simbol Islam, dan bahwa salah satu keutamaan Islam adalah moderasi saat menjalankan urusan agama dan mengeluarkan aturan. Dalam fatwa, gagasan moderasi berpusat pada prinsip memfasilitasi umat Islam dalam menjalankan urusan agamanya. Dalam konteks fatwa MKI saat ini, penelitian ini menemukan bahwa lima fatwa yang dikeluarkan berkaitan dengan urusan Islam dalam krisis pandemi COVID-19. Temuan penelitian ini menjelaskan bahwa setiap fatwa memiliki ciri moderasinya sendiri.